Pop-Up Book Learning Media Assisted by Augmented Reality to Increase Reading Interest in the Concept of Hindu Kingdoms in the Archipelago - Nyoman Sutrana, Kadek Erik Apriliawan; Desak Putu Parmiti; Kadek Yudiana (Universitas Pendidikan Ganesha, 2025)
Students' reading interest in history learning is still low because the presentation is not interactive enough. One of the challenging materials is the concept of the Hindu Kingdom in the Archipelago, which is abstract and difficult to understand without visualization. This study aims to analyze the effectiveness of pop-up book media assisted by augmented reality (AR) in increasing reading interest and understanding of fourth grade students. This study is a developmental research using the ADDIE (Analyze, Design, Development, Implementation, and Evaluate) development model. The subjects of the study were 17 fourth grade elementary school students. The data collection methods and instruments used were questionnaires. Data analysis techniques were carried out descriptively quantitatively and qualitatively. The results of the study showed that this media significantly increased students' reading interest and understanding. Students were more enthusiastic and active, and showed an increase in understanding scores. The implication of this study is that AR technology can be an innovative solution in history learning. However, the limitations of AR devices in schools are still a challenge that needs to be overcome in further research.